2021
DOI: 10.7759/cureus.17096
|View full text |Cite
|
Sign up to set email alerts
|

Acute Anemia and Myocardial Infarction

Abstract: Various studies have established the prognosis of anemia in myocardial infarction (MI). Both chronic and acute anemia lead to poor outcomes in MI. Regardless, the association of anemia with MI and its management varies. In this study, the literature was analyzed to determine the association between acute anemia and MI based on the pathophysiology, outcomes, and management options. Acute anemia results in decreased blood supply and sudden hypoxia to the heart. Additionally, it exacerbates the preexisting compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
1
6
0
2
Order By: Relevance
“…Thus, there is a disproportionate oxygen supply and demand ratio to the heart. It was found that anemia increases all-cause mortality in acute MI [25]. In the present study, the CK-MB and the troponin T hs levels were significantly increased in diabetic patients with high RDW levels.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, there is a disproportionate oxygen supply and demand ratio to the heart. It was found that anemia increases all-cause mortality in acute MI [25]. In the present study, the CK-MB and the troponin T hs levels were significantly increased in diabetic patients with high RDW levels.…”
Section: Discussionsupporting
confidence: 57%
“…Anemia is a medical condition generally identified by a decrease in the blood’s ability to carry oxygen. This condition can worsen the imbalance between the demand and supply of oxygen in the heart muscle, increasing the likelihood of experiencing an MI [ 40 ]. Additional research is necessary to clarify the underlying mechanisms that connect anemia with the risk of MI.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest effect of IDA may be due to stimulated oxidative stress, decreased blood supply, myocardial hypoxia, and the close interplay of the outcomes. 92 , 93 Additionally, we assume the intake of psychotropic medications may exacerbate the susceptibility because they are known to cause undesirable cardiometabolic effects. 94 , 95 A much lower chance of adherence to cardiovascular disease medication and health care‐seeking behaviors to prevent physical illness among many patients with psychiatric disorders (especially those with severe mental illness) might also contribute to an increased risk of MI events.…”
Section: Discussionmentioning
confidence: 99%